Evaluation of the Infantile Colic Causes in Persian Medicine - Mohammad Hosein Asadi; Saeed Changizi-Ashtiyani; Seyed Amir Hossein Latifi (Mashhad University of Medical Sciences, 2021)
Background: Infantile colic is a common condition among neonates; however, its etiology is not fully identified. Thisstudy aimed to evaluate this complication and search for treatments by investigating the experiences of Iranianphysicians.Methods: In this review study, the infantile colic was initially studied in modern medicine. To this end, an electronicsearch was performed in databases, such as Web of Science, Medline (via PubMed), Scopus, EBASE, UpToDate(International databases), Magiran, SID, Irandoc, IranMedex (National databases), and the Google Scholar searchengines. Subsequently, this complication was investigated in the original references of Persian medicine. In this regard,the words related to the subject matter of the research were taken from the original books of Iranian medicine,including Al-Mansouri Fi Al-Tibb, Canon, Kholasatol Hekmah, and Kholasat Al-Tajarob.Results: The results of this study indicated that factors, such as maternal mood during pregnancy, inappropriatematernal nutrition, gastrointestinal problems, and infantile cerebral problems are some of the causes that have beenmentioned regarding infantile colic in modern and Persian medicine. Other causes, such as spinal nerve stimulation,insomnia, and sleep apnea are also raised in Persian medicine. Almost all of these causes are due to poor digestion ofmilk and pneuma in the gastrointestinal tract. Iranian physicians have considered solutions, such as massage withspecial oils, nutrition modification, and the use of hypnotics to reduce pneuma production in the gastrointestinal tractas well as its side effects. The application of these recommendations together can help better treat infantile colic. Inthis regard, the data were categorized by reviewing the works of Iranian scholars, as well as combining modernmedical findings and Iranian experience. Accordingly, a new definition of colic can be provided and some newtreatments are added for infantile colic based on modern and traditional medicineConclusion: Since the positive role of some measures, such as massage and swaddling in modern medicine isconfirmed, the investigation and recommendations of Iranian physicians in the field of infantile colic seem to be able tocompensate for the gap in identification, prevention, and treatment of this complication.